STUDY OF THE SEAHHORSE POPULATIONS IN TWO ZONES OF THE NORTH COAST OF HAVANA AND PINAR DEL RÍO, CUBA - Pastor-Gutiérrez, Lourdes (2011)
This paper presents the results of the study on seahorse populations at two stations located in the north coast of La Habana and Pinar del Río, Cuba. Visual census were conducted by free divers, using the linear transect method between April 2004 and June 2005. Mean density was obtained for the species Hippocampus reidi (Ginsburg, 1933) and Hippocampus erectus (Perry, 1810), by stations and by seasons of the year. H. reidi was the most abundant species and the biggest density was present in Las Cuarenta station 0.0109 ind/m2. No differences were found regarding density between the rainy and dry seasons for the studied species. Male and female H. reidi showed similar sizes (LT). A monogamous behavior of the species H. reidi is inferred due to the sexual proportion found, which is very similar to the expected proportion of 1:1.